Comparative Characteristics of the Traditional Method in Preparing Cards for Edition and Using Computer Technologies - Minashkina N.A; Shchukina O.G. (Zien Journals, 2023)
This article discusses the results of a comparison of two methods for creating maps when preparing them for publication - this is the traditional method using photocopy frames, centrifuges, phototypesetters designed to make dissected positives on plastic according to the elements of the map content, and the method using the AGFA AVANXIS IV digital station for making digital card positives. The concept of blue copies, colorful samples, phototypesetter and digital cards, which are obtained using computer technology programs, is given. The concept of photocopying processes is described when creating publishing originals made by the traditional method and with the help of computer technology.
Keywords: blueprint frame; phototypesetter; centrifuge; publisher's original